A feasibility model for determining the number of inserted additional freight train in existing single-track train schedule. (30th September 2022) - Rusdiansyah, Ahmad; Sari, Arrifah Ratna; Iswardani, Kurnia
The delivery of goods via railways is more frequently done during the nightshift. With the increase in the demand for goods delivery service, there is a need to maximise the capacity in the more available afternoon shift. This research was conducted using a heuristic technique that uses a mathematical model mixed integer linear programming to maximise the number of freight trains that can be added in a single-track train schedule with overtaking strategy. The results showed the minimum headway effect on the number of additional freight trains. The optimum minimum headway is six minutes. With this minimum headway, the freight train that can be added is 20 trains with 15 trains arriving at the destination station on time and the other 5 trains will incur delay not exceeding 3 hours. The increase in the carrying capacity is 1, 200 TEUs/day. When compared with the initial capacity, it means that the addition of transport capacity can reach up to 28.57%.